Medical Tourism: A Fad or an Opportunity; Comment on "Patient Mobility in the Global Marketplace: A Multidisciplinary Perspective" - Nabil Kronfol (Kerman University of Medical Sciences, 2014)
This article is a commentary of an overview on "medical tourism" submitted by Lunt and Marrion, which describes a framework for the study of the issues related to medical tourism. The commentary attempts to differentiate between the current interest in medical tourism and the time-honored and well-established treatment abroad from countries with underdeveloped health systems. The commentary also calls for efforts to strengthen medical services and quality of care through the inflow of patients to countries that attract "medical tourists".